Hospital Phenotypes in the Management of Patients Admitted for Acute Myocardial Infarction. Issue 10 (October 2016) - Xu, Xiao; Li, Shu-Xia; Lin, Haiqun; Normand, Sharon-Lise T.; Lagu, Tara; Desai, Nihar; Duan, Michael; Kroch, Eugene A.; Krumholz, Harlan M.
Abstract : Objectives: To characterize hospital phenotypes by their combined utilization pattern of percutaneous coronary interventions (PCI), coronary artery bypass grafting (CABG) procedures, and intensive care unit (ICU) admissions for patients hospitalized for acute myocardial infarction (AMI). Research Design: Using the Premier Analytical Database, we identified 129, 138 hospitalizations for AMI from 246 hospitals with the capacity for performing open-heart surgery during 2010–2013. We calculated year-specific, risk-standardized estimates of PCI procedure rates, CABG procedure rates, and ICU admission rates for each hospital, adjusting for patient clinical characteristics and within-hospital correlation of patients. We used a mixture modeling approach to identify groups of hospitals (ie, hospital phenotypes) that exhibit distinct longitudinal patterns of risk-standardized PCI, CABG, and ICU admission rates. Results: We identified 3 distinct phenotypes among the 246 hospitals: (1) high PCI—low CABG—high ICU admission (39.2% of the hospitals), (2) high PCI—low CABG—low ICU admission (30.5%), and (3) low PCI—high CABG—moderate ICU admission (30.4%). Hospitals in the high PCI—low CABG—high ICU admission phenotype had significantly higher risk-standardized in-hospital costs and 30-day risk-standardized payment yet similar risk-standardized mortality and readmission rates compared with hospitals in the low PCI—high CABG—moderate ICU admission phenotype. Hospitals in these phenotypes differed by geographic region. Conclusions: Hospitals differ in how they manage patients hospitalized for AMI. Their distinctive practice patterns suggest that some hospital phenotypes may be more successful in producing good outcomes at lower cost. Abstract : Supplemental Digital Content is available in the text.